Influence of powder characteristics of reactive alumina on properties of alumina-spinel castables. Issue 8 (1st June 2018) - Zhang, Danyang; Li, Chunxue; Jiang, Nian; Gao, Jianying; Touzo, Bruno; Yuan, Wenjie
Abstract: Alumina-spinel castables have a broad range of applications in high temperature industries. To explore the influence of different powder characteristics of various reactive alumina additions, properties of alumina-spinel castables calcined at different temperatures (1500 °C and 1650 °C) were investigated. Rheological behaviors of the matrix of different castables were compared. It was demonstrated that the slurry of matrix containing reactive alumina (A) with largest specific surface area and activity had the lowest viscosity at high shear rates. This was beneficial to the molding of castables. For fine reactive alumina powders, differences in the expansion and porosity of castables were attributed to the mineralogical and microstructural evolution, which were affected by the particle size and Na2 O impurity level. The formation of calcium hexaluminate (CA6 ) and CM2 A8 played important role in enhancing the strength of castables.